Household debt, heterogeneity and financial stability: Evidence from Kazakhstan - Alisher Aldashev; Birzhan Batkeyev (Central Bank Review (CBR), 2023)
Using a Monte Carlo method and quarterly data from the 2019 Household Expenditure and Income Survey, we examine the resilience of urban and rural households to various shocks, including exchange rate change, changes in asset prices, job losses, and decline in income. Based on the exposure at default (EAD) estimates, the largest impact was observed in the case of an income shock. The EAD values ranged from 0.38 to 0.43 compared to a baseline case of 0.35. The latter indicates that about one-third of the debt held by households may be problematic, especially in rural areas. The second largest impact is seen for a major currency devaluation, followed by the rise in unemployment. In addition, the breakdown of these results by income shows that households in the lower income quartiles are more vulnerable. Potential implications are discussed.
Keywords: D10; D14; D31; E17; 330; Financial stability; Household debt; Stress testing